Inhibition of midbrain cholinergic neurons impairs decision-making strategies during reversal learning - Kim, Yuwoong; Gut, Nadine K.; Shiflett, Michael W.; Mena-Segovia, Juan (Frontiers in Molecular Neuroscience, 2024)
IntroductionThe pedunculopontine nucleus (PPN) plays a role in coordinating complex behaviors and adapting to changing environmental conditions. The specific role of cholinergic neurons in PPN function is not well understood, but their ascending connectivity with basal ganglia and thalamus suggests involvement in adaptive functions.MethodsWe used a chemogenetic approach in ChAT::Cre rats to explore the specific contribution of PPN cholinergic neurons to behavioral flexibility, focusing on the adaptation to shifting reward contingencies in a Reversal Learning Task. Rats were first trained in a non-probabilistic reversal learning task, followed by a probabilistic phase to challenge their adaptive strategies under varying reward conditions.ResultsMotor functions were evaluated to confirm that behavioral observations were not confounded by motor deficits. We found that inhibition of PPN cholinergic neurons did not affect performance in the non-probabilistic condition but significantly altered the rats’ ability to adapt to the probabilistic condition. Under chemogenetic inhibition, the rats showed a marked deficiency in utilizing previous trial outcomes for decision-making and an increased sensitivity to negative outcomes. Logistic regression and Q-learning models revealed that suppression of PPN cholinergic activity impaired the adaptation of decision-making strategies.DiscussionOur results highlight the role of PPN cholinergic neurons in dynamically updating action-outcome expectations and adapting to new contingencies. The observed impairments in decision-making under PPN cholinergic inhibition align with cognitive deficits associated with cholinergic dysfunction in neurodegenerative disorders. These findings suggest that cholinergic neurons in the PPN are essential for maximizing rewards through the flexible updating of behavioral strategies.